2018
DOI: 10.1128/mcb.00010-18
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intestinal Epithelial Barrier Function by Long Noncoding RNA uc.173 through Interaction with MicroRNA 29b

Abstract: The mammalian intestinal epithelium establishes a selectively permeable barrier that supports nutrient absorption and prevents intrusion by noxious luminal substances and microbiota. The effectiveness and integrity of the barrier function are tightly regulated via well-controlled mechanisms. Long noncoding RNAs transcribed from ultraconserved regions (T-UCRs) control diverse cellular processes, but their roles in the regulation of gut permeability remain largely unknown. Here we report that the T-UCR enhances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…3 Intestinal epithelial cells (IECs), connected by apical intercellular junctional complexes named tight junctions (TJs) and adherens junctions (AJs), establish a selectively permeable barrier that protects the subepithelial tissue against luminal noxious substances, but they also react to noxious stimuli by secreting different antimicrobial peptides and proteins. 4,5 Paneth cells that reside at the bottom of the crypts produce high quantities of defensins and other antibiotic proteins such as lysozyme, Reg3 lectins, and phospholipase A2 when exposed to pathogenic bacteria and bacterial products such as lipopolysaccharide (LPS). 6 In response to bacterial infection of the intestines, Paneth cells secrete lysozyme through secretory autophagy 7 and their function is tightly regulated at the posttranscriptional level by the RNA binding protein HuR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Intestinal epithelial cells (IECs), connected by apical intercellular junctional complexes named tight junctions (TJs) and adherens junctions (AJs), establish a selectively permeable barrier that protects the subepithelial tissue against luminal noxious substances, but they also react to noxious stimuli by secreting different antimicrobial peptides and proteins. 4,5 Paneth cells that reside at the bottom of the crypts produce high quantities of defensins and other antibiotic proteins such as lysozyme, Reg3 lectins, and phospholipase A2 when exposed to pathogenic bacteria and bacterial products such as lipopolysaccharide (LPS). 6 In response to bacterial infection of the intestines, Paneth cells secrete lysozyme through secretory autophagy 7 and their function is tightly regulated at the posttranscriptional level by the RNA binding protein HuR.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Recent evidence has indicated that lncRNAs are an emerging class of master regulators of intestinal epithelium homeostasis and participate in the control of gut permeability, mucosal growth, and adaptation. 5,[17][18][19] Transcribed from the conserved imprinted H19/igf2 gene cluster, lncRNA H19 is implicated in different cellular processes. 20,21 During embryogenesis, H19 expression levels increase in extraembryonic tissues, in the embryo itself, and in most fetal tissues, but its levels decrease after birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it was seminal the report of a direct interaction of Uc.283+A with pri‐miR‐195 that prevented the cleavage of this last by Drosha and hindered its maturation [193]. Subsequently, other authors have described further T‐UCR/miRNA interactions such as that of Uc.173 with miRNA‐195 [194] or miR‐29b [195] to facilitate function of the intestinal epithelium, or the interaction of Uc.416+A with miR‐153 in renal cell carcinoma [189].…”
Section: Long Non‐coding Rnas (Lncrnas) and Their Functional Relationmentioning
confidence: 99%
“…The silencing of uc.173 causes dysfunction in the intestinal epithelial barrier by inhibiting the claudin‐1 protein, which is important to determine the permeability of this tissue. The regulatory action of uc.173 is also caused by the decoy RNA effect for miR‐29b, which represses claudin‐1 translation (J. Y. Wang et al, ).…”
Section: T‐ucrs Deregulated In Physiologic/pathologic Processesmentioning
confidence: 99%